Sonsuz panayır in terms of economic indicators - Ünlü, Bedirhan (Ahmet BURAN, 2024)
The Turkish novel, which first emerged during the Tanzimat period, began to incorporate new themes with the establishment of the republic. The social, political, and economic changes experienced during this time were integrated into the narrative of the novel. In particular, the economic collapse caused by World War II, along with the rise of "nouveau riche" individuals, deeply influenced socio-economic life and became one of the central themes in novels. The economic inequalities resulting from the wartime economy and the subsequent social changes became focal points for artists. Halide Edib Adıvar is among the authors who began their literary careers during the National Literature period and continued to develop their artistic identity during the Republic period. In her novel Sonsuz Panayır (The Endless Fair), the author centers on the impact of the economic conditions that emerged during the Republic period on social life. The novel portrays the lives of the newly wealthy class that emerged after World War II, as well as those from the middle and lower income groups. To illustrate the economic conditions affecting the social environment, the cast of characters is expanded. The characters in the novel are leading figures within their respective social and economic classes. Economic conditions are depicted within the framework of a grand fair. Sonsuz Panayır was written on the cusp of the economic paradigm shift that would occur in Turkey after World War II. During this period, the economic vacuum created by the war was filled by the black market and smugglers, giving rise to an artificial wealthy class in society. The novel’s protagonist, Ayşe, attempts to climb the social ladder by moving to a neighborhood inhabited by the nouveau riche, through which the economic living conditions of the period are revealed. The new economic structure that emerges in this setting is founded on two contrasting economic ideologies. The state-based economic model and the capitalist-oriented economic approach represent two distinct economic schools that are reflected through the novel’s large cast of characters. This study also explores the economic structure of the period, as reflected through the novel's characters and settings.

Tanzimat’la ilk örneklerini veren Türk romanı, Cumhuriyet’le birlikte yeni temaları bünyesinde barındırmaya başlar. Sosyal, siyasi ve iktisadi anlamda yaşanan değişmeler romanın konusuna dâhil edilir. Özellikle İkinci Dünya Savaşı’nın neden olduğu iktisadi çöküşün yanı sıra “türedi zenginler” de sosyo-ekonomik hayatı derinden etkilerken romanlarda da işlenen konulardan birisi hâline gelir. Savaş ekonomisinin neden olduğu gelir düzeyindeki adaletsizlik ve ortaya çıkan sosyal değişim sanatçıların üzerinde durduğu konulardır. Halide Edip Adıvar da ilk eserlerini Millî Edebiyat Dönemi’nde vermeye başlayıp sanatçı kimliğini Cumhuriyet Dönemi’nde devam ettiren yazarlardandır. Yazar, kaleme aldığı Sonsuz Panayır’da Cumhuriyet Dönemi’nde ortaya çıkan iktisadi yaşam koşullarının toplumsal hayata etkilerini merkeze alır. Romanda İkinci Dünya Savaşı’yla birlikte zenginleşen sınıf ile orta ve alt düzey gelir grubuna sahip insanların hayatlarından kesitler aktarılır. Sosyal ortamı etkileyen iktisadi koşulların ayrıntılarını vermek amacıyla romanın şahıs kadrosu genişletilir. Romanın şahıs kadrosu, farklı sosyal ve iktisadi özellikleriyle mensubu oldukları sınıfların önde gelen isimleridir. İktisadi hayat koşulları, büyük bir panayır etrafında aktarılır. Sonsuz Panayır İkinci Dünya Savaşı’nın ardından Türkiye’de yaşanacak olan iktisadi ekolün değişim eşiğinde kaleme alınır. Bu yıllarda savaşın getirdiği ekonomik boşluk, karaborsa ve kaçakçılar tarafından doldurularak toplumda yapay bir zengin sınıfı türemiştir. Romanın başkarakteri Ayşe’nin sınıf atlamak için türedi zenginlerin yaşadığı semte gitmesiyle dönemin iktisadi temeldeki yaşam şartları gözler önüne serilir. Karşılaşılan yeni ortamla birlikte ortaya çıkan iktisadi yapılanmanın temelinde iki farklı düşünce yer alır. Devlet temelli iktisat modeli ile kapitalist eğilimli iktisadi yaklaşım romandaki geniş şahıs kadrosunun dâhil olduğu iki farklı ekonomi ekolünü temsil ederler. Yapılan bu çalışmada da romanın kişiler ve mekânlarından hareketle döneme yansıyan iktisadi yapı ortaya konulmuştur.
İKTİSADİ GÖSTERGELER AÇISINDAN SONSUZ PANAYIR
Keywords: Modern Turkish Literature in Turkiye Field; Türkiye Sahası Yeni Türk Edebiyatı